Pemberdayaan Kader Kesehatan melalui Pembentukan Kelompok “Mapia” Mahir Pijat Bayi disertai Murottal untuk Mengoptimalkan Perkembangan Bayi di Desa Bambu, Mamuju, Sulawesi Barat - Supratti; Andi Nasir; Syamsidar; Iswan HR; Zauqiah Putri Ramadhani; Nur Adillah (CV. CENDIKIA JENIUS INDONESIA, 2024)
Baby massage offers significant benefits, such as strengthening the bond between mother and child, improving weight gain, and optimizing the baby’s development. The goal of this community service activity is to enhance the knowledge and skills of health cadres through the